1999
DOI: 10.1121/1.427041
|View full text |Cite
|
Sign up to set email alerts
|

Seabed sediment attenuation profiles from a movable sub-bottom acoustic vertical array

Abstract: The acoustic lance ͓S. S. Fu, M.Sc. Thesis, University of Hawaii at Manoa ͑1994͒; Fu et al., J. Acoust Soc. Am. 99, 234-241 ͑1996͔͒ consists of a linear array of acoustic receivers below an acoustic source, all mounted on the outside of a core barrel or independent probe which is embedded in the seafloor. In earlier studies lance travel time data were processed to give in situ compressional wave sound speed as a function of depth. In this study lance waveforms are processed to extract compressional wave attenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…Higher amplitudes of the self-normalized acoustic signal were noticed when emitted in the water column than in the sea£oor (C, top). Water reference signals obtained at Site S90 (after Frazer et al, 1999) revealed a subtle di¡erence in frequency response of the individual transducers and di¡erent waveforms when recorded in sediments (C, bottom).…”
Section: Calculation Of In Situ Acoustic Compressional Wave Sound Speedmentioning
confidence: 99%
See 4 more Smart Citations
“…Higher amplitudes of the self-normalized acoustic signal were noticed when emitted in the water column than in the sea£oor (C, top). Water reference signals obtained at Site S90 (after Frazer et al, 1999) revealed a subtle di¡erence in frequency response of the individual transducers and di¡erent waveforms when recorded in sediments (C, bottom).…”
Section: Calculation Of In Situ Acoustic Compressional Wave Sound Speedmentioning
confidence: 99%
“…2C, top). Waveforms from this calibration allowed us to determine the exact spacing between the acoustic centers of the individual receiver elements, and then to calculate attenuation (Frazer et al, 1999). After the water calibration, the corer freefell to the sea£oor and penetrated the subbottom to a depth that depended primarily on the shear strength of the sediment.…”
Section: Calculation Of In Situ Acoustic Compressional Wave Sound Speedmentioning
confidence: 99%
See 3 more Smart Citations